Diagnóstico energético del proceso productivo en trapiches de las veredas El plan, El Pueblo y San Fernando en el corregimiento del Ingenio – Municipio de Sandoná - Nariño - Hernandez Villota, David Alexander; Martinez Benavides, Edwin Adolfo (Universidad Antonio Nariño, 2022)
— In the corregimiento of El Ingenio in the municipality of Sandoná - Nariño, the production of panela represents one of the main economic contributions of the region, with the department of Nariño being one of the 14 departments with the highest production in Colombia. The production process is carried out in an artisanal way through trapiches (sugar mills), this generates considerable energy consumption that affects production costs and has a negative environmental impact. Due to this, this descriptive research project was developed where, following the guidelines of the ISO 50001 standard, the production process of 4 trapiches in the corregimiento El Ingenio is energetically characterized, this in order to generate a baseline for the implementation of integral energy management in these productive processes. As a result of the investigation, a characterization of the panela production procedures and an energy diagnosis of the trapiches used in them was conducted, obtaining that about 48% of the production process depends on electrical and heat energy, in addition to the opportunity to technological innovations and implementations that improve productivity and efficiency in the production process.